Development of Digital Teaching Materials for Explanatory Texts: Integration of Genre Pedagogy, Literacy, and Critical Thinking for Junior High School - Elly Sofiar; Nani Solihati; Zamah Sari (STAI Hubbulwathan Duri, 2025)
This study investigates student needs as the initial stage in developing digital teaching materials for Indonesian explanatory texts. The materials are designed using an integrated genre pedagogy that enhances both literacy skills and critical thinking. The research employed a descriptive quantitative approach using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Data were collected from 65 eighth-grade junior high school students using a validated and reliable questionnaire. The instrument underwent validation and reliability testing to ensure data accuracy. Analysis was conducted using SPSS version 27. Findings revealed that 80% of students (28% strongly agree, 52% agree) support the development of digital teaching materials integrating genre pedagogy and critical thinking. Only 2% of respondents expressed disagreement. These results indicate a strong student preference for instructional content that promotes both literacy and critical thinking through structured genre-based approaches. The data suggest a significant demand among students for digital teaching materials that align with contemporary literacy and thinking skill development. The results will guide the next phases of teaching material design and development in the larger research project.